Assessing the Dynamics of Sukuk Research on Scopus Database: A Bibliometric Analysis and Systematic Literature Review - Arif, Arif; Mulyati, Sri; Handoko, Lukman Hakim (Equilibrium: Jurnal Ekonomi Syariah, 2024)
This research aims to determine the dynamics of sukuk research on the Scopus database. This research has three novelties: choosing more complex keywords, standardizing keywords, and explaining complex future research findings. This research employs a mixed method, using both quantitative and qualitative approaches. The quantitative method in this research uses simple statistical techniques through bibliometric analysis. Meanwhile, the qualitative method uses a systematic literature review approach. This research uses secondary data taken from the Scopus database. The data analysis software used is VOSviewer. The research results show that based on its distribution, research on sukuk was first published in 2007, and as of October 2023, there were 524 documents. Based on productivity, the most productive writer is Nader Naifar from Imam Mohammad Ibn Saud Islamic University (14 documents), Malaysia's most productive country (170 documents). Based on his popularity, the most popular author is Godlewski C.J. (186 citations). Based on trends, the frequently appearing keywords are sukuk, the newly used keywords are green finance, and the rarely used keywords are blockchain. Based on future research directions, there are recommendations for 96 topics that can be researched. This research is beneficial for future sukuk research and supporting global sukuk practice.